Increased fascial thickness of the deltoid muscle in dermatomyositis and polymyositis: An ultrasound study. Issue 4 (20th August 2015) - Bhansing, Kavish J.; Van Rosmalen, Marieke H.; Van Engelen, Baziel G.; Vonk, Madelon C.; Van Riel, Piet L.; Pillen, Sigrid
ABSTRACT Introduction: We investigated the use of ultrasound to detect fascial thickening of the deltoid, vastus lateralis (VL), and rectus femoris (RF) muscles in dermatomyositis (DM) and polymyositis (PM). Methods: Fascial thickness of 7 DM and 5 PM patients was compared with that of healthy controls (n = 54). Results: The deltoid fascial thickness was 2‐fold greater in the DM/PM group (1.15 mm vs. 0.54 mm; P < 0.001) compared with healthy controls. Eight patients had markedly thickened deltoid fascia (>5 SD). Only 1 patient with a mild clinical presentation had normal deltoid fascial thickness. Four patients also had fascial thickening of the VL and/or RF. Conclusions: Deltoid fascial thickness was increased significantly in DM and PM patients, whereas the quadriceps muscle only showed thickened fascia in severely affected patients. This study suggests that a concomitant fasciitis may be present more often than previously believed. Muscle Nerve, 2015 Muscle Nerve 52: 534–539, 2015